Instagram Features as Media for Learning English Listening Comprehension - Ridha Mardiani; Nisrina Syifa Ursila (Universitas Subang, 2024)
This study aimed to investigate what Instagram features that help students in learning English listening comprehension, and to find out the students’ perceptions towards Instagram as a media to learn the subject. Mixed method was used for this study, specifically in the form of a case study in one secondary school in Cimahi, West Java, Indonesia. Ten secondary school students aged between 15 and 18 years were chosen as participants of this study. The researchers tried to create Instagram content that would help the students learn the subject, combined with the use of questionnaires, classroom observation, and students’ interview to obtain data. Data from questionnaires were analyzed using percentage calculation, data from classroom observation were analyzed based on the activities in the classroom and displayed in the form of table, while students’ interview were analyzed based on deductive thematic data analysis. The result shows that the students are familiar with Instagram Story, Post, Reel, and Live. These Instagram features were used as tools for learning English Listening comprehension. The students perceived that the use of Instagram features for listening English comprehension could help them develop their potencies, make the learning materials more interested, assist them to learn and be more creative.